Polycystic ovary syndrome negatively affects sexual function and lower urinary tract symptoms in syrian women: a case-control study - Ali Alshiekh; Rana Hadakie; M Fadi Al Kurdi; Luna sukkar; Marwan Alhalabi; Hamoud Hamed (Scientific Reports)
Abstract Polycystic ovary syndrome (PCOS) is the most prevalent endocrine disorder in women of reproductive age worldwide, and its related features like obesity, mental health issues and hyperandrogenism may contribute to inadequately investigated health problems such as sexual dysfunction (SD) and lower urinary tract symptoms (LUTS). Therefore, this study examined the impact of PCOS on sexual function (SF) and lower urinary tract in Syrian women by recruiting a total of 178 women of reproductive age, of whom 88 were diagnosed with PCOS according to the Rotterdam criteria and 90 without PCOS were considered as the control group. Female sexual function index (FSFI) and Bristol Female Lower Urinary Tract Symptom Questionnaire (BFLUTS) were used to assess SF and LUTS respectively. PCOS group had higher SD prevalence compared to control group (65.9% vs 48.9%, p = 0.016), and BMI showed an inverse correlation with the total FSFI score in PCOS group (p = 0.027, r = -0.235). Furthermore, PCOS group exhibited significantly lower scores in orgasm and satisfaction subdomains. Additionally, PCOS patients had significantly higher total BFLUTS score compared to control group (median 8 vs 5, p = 0.025). Thus, PCOS may be related to SD and LUTS, highlighting the importance of evaluating SF and urinary symptoms in PCOS patients.